Preseason strategies of Italian first league soccer clubs in relation to their championship ranking: A five-year analysis - Massimo Francioni, F.; Figueiredo, A. J.; Lupo, C.; Conte, D.; Capranica, L.; Tessitore, A. (Journal of Human Kinetics, 2016)
This study is focused on the strategies adopted by Italian `Serie A` soccer clubs during the non-competitive period. Thus, duration (i.e., number of days) of the specific non-competitive periods (i.e., off- plus pre-season, off-season, pre-season, summer camp), the number of games (i.e., friendly, official and polled games) and days between games (i.e., = 3, 4-5, or = 6 days between two consecutive games) of the entire non-competitive period were recorded and compared by clubs participating in the European Championships (EU), only `Serie A` (A) and promoted from `Serie B` (B) during five and single seasons (i.e., 2009/10-2013/14). Due to the short B off-season duration (2009/10-2013/14, 2010/11, 2011/12, 2012/13, 2013/14, p=.001), effects between clubs emerged also for the off- plus preseason (2009/10-2013/14, EU vs A, p=.01, EU vs B, p=.01, A vs B, p=.001; 2011/12, 2012/13, 2013/14, p=.001). Nevertheless, no difference between clubs resulted for the pre-season. Reduced duration of summer camps was reported by the EU (i.e., 2009/10-2013/14, 2009/10, 2013/14, p=.001). A higher number of official games were played by EU than A (i.e., 2009/10-2013/14, p=.001; 2010/11, p=.01). No effect emerged for the days between games. Therefore, despite the longer `Serie B` schedule and EU preliminary UEFA games that determined the off-season restriction, clubs demonstrated the tendency to guarantee satisfactory pre-season duration.